GIGANTEA supresses wilt disease resistance by down-regulating the jasmonate signaling in Arabidopsis thaliana - Patnaik, Alena; Kumar, Aman; Behera, Anshuman; Mishra, Gayatri; Dehery, Subrat Kumar; Panigrahy, Madhusmita; Das, Anath Bandhu; Panigrahi, Kishore C. S. (Frontiers in Plant Science, 2023)
GIGANTEA (GI) is a plant-specific nuclear protein, that plays pleiotropic functions in the growth and development throughout the plant's life. GI’s involvement in circadian clock function, flowering time regulation, and various types of abiotic stress tolerance are well documented in recent years. Here, the role of GI in response to Fusarium oxysporum (F. oxysporum) infection is investigated at molecular level comparing Col-0 WT with gi-100 mutant in Arabidopsis thaliana. Disease progression, photosynthetic parameters, comparative anatomy confirmed that the spread and damage caused due to pathogen infection was less severe in gi-100 than in Col-0 WT plants. F. oxysporum infection induces a remarkable accumulation of GI protein. Our report showed that it is not involved in flowering time regulation during F. oxysporum infection. Estimation of defense hormone post infection showed that Jasmonic acid level is higher and salicylic acid level is lower in gi-100 compared to Col-0 WT. Here we show that the relative transcript expression of CORONATINE INSENSITIVE1 (COI1) and PLANT DEFENSIN1.2 (PDF1.2) as a marker of JA pathway is significantly higher while ISOCHORISMATE SYNTHASE1 (ICS1) and NON-EXPRESSOR OF PATHOGENESIS-RELATED GENES1 (NPR1), the markers of SA pathway are down regulated in the gi-100 mutants than Col-0 plants. The present study convincingly suggested GIGANTEA module promotes susceptibility to F. oxysporum infection by inducing SA pathway and inhibiting JA signalling in A. thaliana.